KARAKTERISTIK FISIK, KIMIA, DAN SIFAT ORGANOLEPTIK YOGHURT DENGAN CAMPURAN BERBAGAI KONSENTRASI SARI LIDAH BUAYA (Aloe vera) - - Adriyan; Siti Aminah (Jurnal Pangan dan Gizi, 2012)
Yoghurt is a beverage product derived from cow's milk that has a slightly sour taste as fermented by Lactic Acid Bacteria (LAB). Aloe vera has a content of nutrients including calcium, potassium, magnesium, vitamin A, B1, B2, B6, B complex, vitamin C, vitamin E, and protein. Need to develop into juice of aloe vera as a material added in yoghurt. The aim of study are test of pH, viscosity, total acid, fiber, and the organoleptic properties of aloe vera yoghurt. The method used is experiment with a completely randomized design (CRD) 1 factor that is with a mixture of aloe vera juice 0%, 5%, 10%, 15% and 20%. The results: pH are respectively 4.99, 5.05, 4.88, 4.87, 4.83; viscosity are 3.59 cP, 5.12 cP, 4.15 cP, 3.32 cP, 2.97 cP; total acid 0.93%, 0.95%, 1.00%, 1.00%, 1.01%; fiber content are 4.07%, 4.15%, 4.17%, 4.22%, 4.27%. The higher mix of aloe vera juice at yogurt, the lower the pH and viscosity. The best Organoleptic quality in the mixing of 5% that taste sour yogurt, viscosity viscous, sour aroma, and color white. Keywords: aloe vera juice, yoghurt, physical, chemical and organoleptic